2017
DOI: 10.1007/s11746-017-2988-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperatures and Duration of Heating on Olive Oil Properties for Food Use and Biodiesel Production

Abstract: Heating deteriorates the physicochemical properties of a vegetable oil for both edible and biofuel uses. The parameters for edible olive oil are established by European Union regulations and by the International Olive Council. The properties of a vegetable oil to be used as a source for biodiesel production are indicated by the German DIN 51605 for rapeseed oil. Biofuel properties are described by the European EN 14214 and the North American ASTM 6751 standards for biodiesel. It is useful to know how temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Results of both AA methods and TPC are shown in Table . ABTS + and DPPH ˙ assays are commonly used to evaluate the AA in olive oil (Baiano et al, ; Giuffrè et al, ). Concerning data of the ABTS + assay, the three oils with RDI (T1–T3) showed higher AA values than those of the control treatment, although T1 and T3 showed higher values than T2.…”
Section: Resultsmentioning
confidence: 99%
“…Results of both AA methods and TPC are shown in Table . ABTS + and DPPH ˙ assays are commonly used to evaluate the AA in olive oil (Baiano et al, ; Giuffrè et al, ). Concerning data of the ABTS + assay, the three oils with RDI (T1–T3) showed higher AA values than those of the control treatment, although T1 and T3 showed higher values than T2.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the literature, these values were similar to other FAME from different sources such as olive oil (60.76% methyl oleate and 18.45% methyl linoleate) or rapeseed oil (60. 7% methyl oleate and 20.5% methyl linoleate) (Giuffrè et al, ; Raman et al, ). However, other raw materials, such as sunflower, showed different results (32.47% methyl oleate and 56.18 methyl linoleate) (Giuffrè et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…If not, biodiesel should be used in mixtures with diesel, or some additives should be added. This way, much research has been carried out about the characterization or influence of FAME in biodiesel from different sources, such as olive oil (Giuffrè et al, ), tomato seed oil (Giuffrè et al, ), sunflower oil (Giuffrè et al, ), or rapeseed oil (Raman et al, ). Concerning additives, both natural and synthetic antioxidants are used, which scavenge free radicals that would attack unsaturated FAME, extending the storage time of biofuels (Dunn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Shinagawa et al (2017) found in grape seed oil higher content of linoleic acid (72.19 -75.02%) which is health-benefitting fatty acid, followed by oleic acid (14.80 -17.20%) and then palmitic acid (6.26 -6.70%) with PUFA from 72.67% to 75.38%, MUFA from 14.80 to 17.34% and SFA content from 9.72 to 10.22%. In contrary, olive oil has higher content of oleic acid (60.76 -62.74%), then linoleic acid (13.22 -18.45%) and palmitic acid (15.19 -18.71%) characterized with higher MUFA content (62.42 -64.30%), lower PUFA content (13.61 -19.20%) but higher SFA content (18.37 -22.09%) (Giuffrè et al, 2017a). Furthermore, in sunflower seed oil the highest content of linoleic acid (50.89 -55.78%), followed by oleic acid (32.37 -35.69%) and palmitic acid (7.47 -6.44%) with the content of PUFA from 52.49 to 56.24%, MUFA from 32.77 to 36.55% and SFA from 10.99 to 12.54% was observed (Giuffrè et al, 2017b).…”
Section: Introductionmentioning
confidence: 96%